The role of emerging technologies in inclusive innovation: the case of nanotechnology in South Africa. (8th December 2017) - Harsh, Matthew; Woodson, Thomas S; Cozzens, Susan; Wetmore, Jameson M; Soumonni, Ogundiran; Cortes, Rodrigo
Abstract: Inclusive innovation seeks to understand how new technologies can provide benefits for the poor and marginalized. However, the role emerging technologies might play in inclusive innovation is not well understood. We synthesize inclusive innovation frameworks with work on equity and emerging technologies by examining the South African National Nanotechnology Strategy. Through document analysis and interviews, we find that some nanotechnology projects address problems of poor communities. The future nanotechnology workforce also reflects South Africa's diversity. Nanotechnology research supports existing businesses and has helped create some new firms, which might increase employment. Overall, the effort created nanotechnology innovation that is somewhat inclusive in its intent, impact, process, and structure. However, innovation could be more inclusive and just by focusing more on technology transfer systems for disadvantaged communities and on rural development. The case illustrates that combining inclusive innovation and equity frameworks provides more specific policy pathways and deeper understanding of justice.